2012
DOI: 10.5657/fas.2012.0221
|View full text |Cite
|
Sign up to set email alerts
|

Gene Structure and Estrogen-Responsive mRNA Expression of a Novel Choriogenin H Isoform from a Marine Medaka Oryzias dancena

Abstract: The marine medaka Oryzias dancena choriogenin H gene (odChgH) and its mRNA expression during estradiol-17β (E2) exposure were characterized. At the amino acid level, the choriogenin H protein is predicted to possess the conserved repetitive N-terminal region, as well as zona pellucida (ZP) and Trefoil factor family (TFF) domains. At the genomic level, odChgH has an eight-exon organization with a distribution pattern of transcription factor binding sites in the 5′-upstream region, which is commonly found in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
(50 reference statements)
0
6
3
Order By: Relevance
“…The liver-specific induction of RFP signals was consistent in all the RFP-positive larvae, indicating that the liver-dominant regulation of choriogenin H promoter was well manifested in transgenic larvae in response to exogenously introduced EE2. However, in a previous study, it was reported that choriogenin H gene transcripts were detectable in several non-liver organs of adult marine medaka (Lee et al, 2012b), which differs from our findings of liver-exclusive appearance of RFP signals in transgenic larvae. Hence, further studies exploring the regulation mechanisms of the choriogenin H gene in non-liver tissues throughout the life cycle of marine medaka are necessary.…”
Section: Effects Of Larval Age On the Success Of Transgene Expressioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The liver-specific induction of RFP signals was consistent in all the RFP-positive larvae, indicating that the liver-dominant regulation of choriogenin H promoter was well manifested in transgenic larvae in response to exogenously introduced EE2. However, in a previous study, it was reported that choriogenin H gene transcripts were detectable in several non-liver organs of adult marine medaka (Lee et al, 2012b), which differs from our findings of liver-exclusive appearance of RFP signals in transgenic larvae. Hence, further studies exploring the regulation mechanisms of the choriogenin H gene in non-liver tissues throughout the life cycle of marine medaka are necessary.…”
Section: Effects Of Larval Age On the Success Of Transgene Expressioncontrasting
confidence: 57%
“…However, although the general applicability of this transgenic approach to variable salinities could be established, a more accurate quantitative comparison of the effects of salinity might also be needed since salinity conditions have been reported to affect the EE2 uptake by the euryhaline teleost, killifish Fundulus heteroclitus (Blewett et al, 2013). In addition, it has been reported that marine medaka fry acclimated to either freshwater or seawater possessed differential basal levels of choriogenin H transcripts (Lee et al, 2012b). This reinforces the need for further studies of differences in the inducibility of transgene and endogenous gene expression during EE2 exposure under different salinity conditions.…”
Section: Ee2-induced Transgene Expression Under Different Salinity Comentioning
confidence: 99%
“…Because we aimed to examine primarily whether the estrogen-mediated RFP signal would be induced exclusively in the main target organ (i.e., liver) or ubiquitously also in other non-liver organs, we exposed transgenic males to high concentrations of estrogens [1.0 μg L −1 (for E2) and 0.5 μg L −1 (for EE2)]. These exposure conditions had been known to induce robustly endogenous chgH transcripts in male adults or RFP signals in transgenic larvae of this medaka species (Cho et al 2013;Nam et al 2015;Lee et al 2012). We did not consider the evaluation of the lowest-observed-effect concentrations (LOECs) of E2 and EE2 here.…”
Section: Induction Of Rfp Phenotype By Estrogen Exposures In Transgenmentioning
confidence: 99%
“…For example, due to the intrinsic nature of the transgenic regulator (choriogenin H promoter) used in marine medaka, female chgH-rfp transgenics are expected to display a naturally occurring fluorescent phenotype even under non-exposed conditions when they reach the stage of ovarian maturation since the synthesis of choriogenins in the liver would be an essential requirement for the formation of egg membrane. In the case of males also, a previous study has shown that marine medaka adult males could express a small amount of chgH messenger RNAs (mRNAs) in their liver under normal culture conditions, although the fate of the transcribed products in males has not been clearly elucidated yet (Lee et al 2012). Further, exogenous administration of estrogens has potentially induced de novo synthesis of chgH mRNAs in several male tissues, although the quantities of chgH transcripts induced in non-liver tissues were significantly smaller than that in the liver (Lee et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation